New Isometopinae (Hemiptera: Heteroptera: Miridae) from the Oriental Region, with some notes on the genera Alcecoris and Sophianus - Herczek, Aleksander; Popov, Yuri A. (Zootaxa, 2011)
A new isometopine species of the genus Alcecoris McAtee & Malloch, 1924 (A. heissi sp. nov.) is described from Thailand. A check-list of the known species of Alcecoris is presented.